PERENCANAN DALAM PERSPEKTIF ISLAM ( KAJIAN TAFSIR âHADIS TEMATIK) - Wisuda, Endah Tri (Humanistika : Jurnal Keislaman, 2016)
Abstract: In the literature of Management Sciences found a variety of definitions of the meaning of management. However, the definition indicates a process that occurs in a management is the definition made by Ricky W. Griffin which defines management as a process of planning, organizing, coordinating, and controlling resources to achieve the goals and objectives effectively and efficiently. Referring to the order management process, then planning is the most early and decisive step towards the goal of management itself. In our opinion, that the people who are lucky are those who have a good plan in living her life. This is the nature of the planning process in which ideals are translated into action. Sfesifik-measures designed to achieve realistic goals.Key words: Planning, Thematic Hadist, Islam PerspectiveÂ